2017
DOI: 10.18256/2238-510x.2017.v6i2.1800
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação das soluções de Clorexidina e de Hipoclorito de Sódio na descontaminação de cones de guta percha contaminados por Enterococcus faecalis

Abstract: O objetivo deste trabalho foi avaliar a efetividade das soluções de Clorexidina e do Hipoclorito de Sódio na descontaminação de cones de guta percha. O estudo foi realizado em duplicata, e em cada um dos testes cones de guta percha #40 foram utilizados. 24 cones foram contaminados com Enterococcus faecalis. Os cones contaminados foram divididos em grupos, conforme a solução (Clorexidina a 2%, Clorexidina a 0,2% e Hipoclorito de Sódio a 2,5%) e o tempo para a descontaminação (15, 30 e 60 segundos, 2, 5 e 10 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Such findings are contrary to those found in the literature, whose results showed disinfection only within one minute 18,20 . However, some authors have shown that the time of 30 seconds is sufficient 21 , while other studies have shown that 2% chlorhexidine is only effective within 10 minutes 14 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Such findings are contrary to those found in the literature, whose results showed disinfection only within one minute 18,20 . However, some authors have shown that the time of 30 seconds is sufficient 21 , while other studies have shown that 2% chlorhexidine is only effective within 10 minutes 14 .…”
Section: Discussionmentioning
confidence: 98%
“…These microorganisms can adapt to unfavorable conditions when exposed to stressful situations 12,13 . As the gutta-percha cones are the main filling materials and are in constant contact with the periapex, it is crucial that the cones be free of microorganisms in order for the endodontic treatment to be satisfactory 14,15 . Some authors 10,16 , when studying guttapercha cones immediately after they were removed, with sterile clinical tweezers from their respective sealed packages, observed that these materials may be contaminated from the factory.…”
Section: Discussionmentioning
confidence: 99%